Organisational Capacity Building: Readiness for Change in Australian Child Care. Issue 1 (February 2015) - Davis, Elise; Corr, Lara; Gilson, Kim-Michelle; Ting, Christina; Ummer-Christian, Rahila; Cook, Kay; Sims, Margaret
THIS STUDY ASSESSES FAMILY day care educators' readiness for increasing their knowledge and skills in promoting children's social and emotional wellbeing by applying the Transtheoretical Model of Change conceptual framework. Forty-eight educators in one family day care scheme, in a low socioeconomic area of Victoria, Australia participated in telephone interviews. Their readiness to improve children's social and emotional wellbeing was classified according to the stages of change model. A high proportion of educators were classified into the action or maintenance stage. Educators reported a range of activities that they were undertaking such as attending professional development sessions and studying formal early childhood qualifications. While educators were open to increasing their knowledge and skills in promoting children's social and emotional wellbeing, they were juggling many demands. The stages of change model was useful in providing an understanding of the processes and principles for progressing through stages, essential for organisational capacity building.